St. Lucia : Statistical Annex. (IMF Staff Country Reports; Country Report ;, 1999)
This paper reviews economic development in St. Lucia during 1993-98. Economic performance weakened in St. Lucia during 1995-97. Real GDP growth declined to an average of about 2 1\2 percent a year during this period, after averaging more than 6 percent over the previous 10-year period. A key element in this decline was the contraction in banana production by one-third, to 71,000 tons in 1997. Brisk growth in tourism offset this decline to some extent, with annual average real earnings increasing by more than 6 percent.